From Germany to pop charts in Turkey : an analysis of Turkish German musicians’ identity performances through rnbesque music - Karahan, Mehtap (My University, 2022)
Müzik ve medya teknolojilerindeki gelişmelerle birlikte insanlar farklı müzik türlerine erişmeye başladılar. Mecazi olarak, farklı müzik tarzlarının dünyanın çeşitli yerlerine göç etmeye başladığını ve bunun da müziğin melez formlarına yol açtığını söyleyebiliriz. Müzisyenler, farklı müzik türlerini kolaylıkla deneyip miksaj edebilirler ve internet sayesinde müziklerini dünya çapında yaygınlaştırabilirler. Bu “karma/ melez” formlardan biri olan Rnbesk, Türkiye'ye geri dönen ve daha fazla insana ulaşan Türk Alman müzisyenler sayesinde Türkiye'de popüler hale geldi. Bu çalışmanın amacı, seçilmiş Türk-Alman müzisyenlerin kimlik performanslarını Rnbesk müzik videoları üzerinden göç ve melez müzik formları bağlamında analiz etmektir. Türün adından da anlaşılacağı gibi, uzun yıllar tartışma konusu olan arabesk müzikten türeyen özel bir müzik türüdür. Arabesk müzik ve arabesk rap üzerine önemli araştırmalar yapılsa da arabesk ve hip-hop'un birleşimi olan rnbesque tartışmaların dışında bırakılmıştır. Bu çalışma, melez müzik türleri üzerine literatüre yeni bir bakış açısı sunmaktadır. Müzik videosu doğası gereği farklı kültürel formları bir araya getirdiğinden, bu araştırmada müzik videolarını analiz etmek için eklektik bir metodolojik yaklaşım benimsenmiştir. Müzik videolarını ve röportajları analiz etmek için nitel analiz kullanılmıştır. Videolardaki ses ve görüntü ilişkisinin tam olarak anlaşılmasını sağlamak için Andrew Goodwin'in müzik video analiz yöntemi ölçüt alınmıştır. Bu çalışma, araştırma için seçilen müzisyenlerin diasporik kimliklerinin müzik videolarında gözlemlenebileceği ve bu kimliği çeşitli dinleyicilere ulaşmak için kullandıkları sonucuna varmaktadır.

With the advancements in the music and media technologies, people started to have access to different forms of music. We could metaphorically say that different musical styles started to immigrate to various parts of the world, and this led to the hybridized forms of music. Musicians could try and mix different types of music easily and they could also spread their music worldwide thanks to the internet. Rnbesque is one of these “mixed/ hybrid” forms and it became popular in Turkey thanks to the Turkish-German musicians who came back to Turkey to perform and to reach higher numbers of people. The aim of this study is to analyze the identity performances of the selected Turkish-German musicians through rnbesque music videos in relation with immigration and hybrid music forms. As it can be understood from the name of the genre, this is a special type of music derived from arabesque music that has become a subject of discussion for a few decades. Although there has been significant research on arabesque music and arabesque rap, rnbesque, which is a combination of arabesque and hip hop, has been left out of discussions. The current study offers a new perspective to the literature on hybrid forms of music. In this research an eclectic methodological approach has been embraced to analyze the music videos because the nature of music videos combines different cultural forms. To analyze the music videos and interviews, qualitative analysis was used. Andrew Goodwin’s music video analysis method was used to provide a complete understanding of the sound and vision relationship in the videos. This study concludes that the diasporic identity of the musicians selected for the study could be observed in the music videos, and they utilize this identity to reach a variety of listeners.
Keywords: arabesk; Araştırma; Culture; göç; hybridization; Intercultural communication; immigration; Kültür; Kültürlerarası iletişim; melezleşme; Music; Müzik; müzik arabesque; Research; rnbesk; rnbesque